2001
DOI: 10.1074/jbc.m010047200
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/Enhancer-binding Protein β Mediates Interferon-γ-induced p48 (ISGF3-γ) Gene Transcription in Human Monocytic Cells

Abstract: Previous studies have identified a novel interferonstimulated response element-like element, termed ␥-interferon-activating transcription element, within the interferon-stimulating gene factor-3␥ ( Interferon-stimulated gene factor-3 (ISGF3) 1 plays a crucial role in mediating the antiviral, antitumor, and immune responses induced by IFNs. The ISGF3 complex consists of a 48-kDa DNA-binding protein (p48 or ISGF3-␥) and two signal transducer and activators of transcription (STAT) proteins, STAT1 and STAT2. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…One of these is a known transcription factor, C/EBP-␤ (22). An independent study also confirmed that C/EBP-␤ stimulates GATE-regulated transcription (23). In this study we have characterized a novel factor, GBF-1.…”
Section: Fig 8 Ifn-␥-induced Expression Of Gbf-1 a Northern Blot mentioning
confidence: 71%
See 1 more Smart Citation
“…One of these is a known transcription factor, C/EBP-␤ (22). An independent study also confirmed that C/EBP-␤ stimulates GATE-regulated transcription (23). In this study we have characterized a novel factor, GBF-1.…”
Section: Fig 8 Ifn-␥-induced Expression Of Gbf-1 a Northern Blot mentioning
confidence: 71%
“…A C/EBP-␤ consensus sequence (CBS) is present in GATE (Fig. 5B) and is necessary for stimulating transcription in a variety of cells (22,23). The fact that GM-1, GM-2, and GM-3 do not respond to IFN-␥ and have a disrupted CBS indicates that C/EBP-␤ binding site plays a large role in regulating this promoter.…”
Section: Fig 8 Ifn-␥-induced Expression Of Gbf-1 a Northern Blot mentioning
confidence: 99%
“…In mammals, IFNc-induced IRF9 protein expression requires de novo protein synthesis, which results in the discovery of GATE motif-dependent induction of mouse IRF9 (Xiao et al, 1997a). A serial of studies revealed the underlying mechanism: initially, IFNc treatment induces the synthesis of two kinds of transcription factors, C/EBP-b and GBF1, possibly through JAK-STAT signaling pathway; subsequently, the produced transcription factors are activated by IFNc treatment, translocate to nucleus and bind to the GATE motif triggering IRF9 expression (Hu et al, 2002;Kalvakolanu and Roy, 2005;Meng et al, 2005;Roy et al, 2000;Xiao et al, 2001). Therefore, the signaling transduction involved is likely different between GAS-dependent and GATE-dependent induction of zebrafish IRF9 gene by zebrafish IFNc2.…”
Section: Discussionmentioning
confidence: 99%
“…The expression property of mouse IRF9 correlates with the complexity of its promoter structure, which includes multiple potential regulatory elements including NF-jB, GAS, GATE (IFN-gamma-activated transcriptional element), and Myc/Max elements (Rani et al, 2010). GATE motif is first characterized in mouse IRF9 promoter as a binding site of CAAAT/enhancer binding protein-b (C/EBP-b) (Roy et al, 2000;Xiao et al, 1997aXiao et al, , 2001) and GATE-binding factor 1 (GBF1) (Hu et al, 2002;Meng et al, 2005) in response to IFNc treatment. Both C/EBP-b and GBF1 binding to GATE site significantly promotes IRF9 gene transcription (Meng et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Among these proteins, C/EBP-␤ uniquely responds to a variety of extracellular and intracellular signals to mediate a number of responses (37,39). Although the effect of C/EBP-␤ on irf9 is well characterized (70,93), it is not clear whether C/EBP-␤ has any other gene targets in the IFN-signaling pathways. Recently, we noticed that IFN-␥-induced cell death is suppressed significantly in cebpb Ϫ/Ϫ cells, indicating the existence of other potential IFN-induced pathways driven through C/EBP-␤.…”
mentioning
confidence: 99%